Translation Strategies in Subtitling Figurative Language on Batwoman Series - Bastian, Dara Azalia; Sujana, Sujana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This research discussed about subtitling of figurative language in Batwoman drama series. The aims of this research to find kinds of figurative languages used in Batwoman and to identify subtitling techniques used in figurative languages in Batwoman. The researcher use Perrines theory to find figurative language and Gottliebs theory find subtitling strategies. The researcher focused on each characters dialogue, those are Batwoman (Kate Kane), Alice, Luke Fox, The method that the researcher used is qualitative method. The result of this research is the researcher found 83 data in the series. For the figurative, the frequency of the data is 15 similes, 8 metaphors, 2 apostrophes, 24 metonymies, 8 synecdoches, 2 symbols, 18 overstatements, and 6 ironies. For the subtitling strategies, the researcher found 3 expansions, 2 paraphrases, 52 transfers, 24 imitations, 1 transcription, and 1 condensation.